Evaluation, Sustainable Development, and the Environment in the South Pacific - Rosario Turvey (The Evaluation Center at Western Michigan University, 2007)
This article outlines the Results-Based Evaluation (RBE) framework proposed for the ex-post assessment of the National Environmental Management Strategies (NEMS) in 12 small-island developing states (SIDS) in the South Pacific. It gives an overview of the methods and basis of developing an evaluation framework in the context of SIDS in the region. Framework development is a) process-based because it integrated contextual, conceptual and empirical parameters for evaluation design, and b) spatially oriented because it involved vulnerability assessment, situational analysis and workshop-based consultation in Kiribati and Samoa. It concludes that RBE has potential value in the review process for updating the environmental strategies and action plans and for measuring what has been achieved within the managerial process for sustainable development in the region.